Citizenship after liberalism - Denham, Mark E.; Slawner, Karen (New York : P. Lang, 1998)
Citizenship After Liberalism explores contemporary challenges to the liberal concept of citizenship, both philosophical and practical. The authors question whether liberalism has the resources to meet those challenges, and explore what might replace it, if it doesn't. The essays approach this issue from a variety of interpretive perspectives and geographical locations. The volume integrates different literatures, including political theory, political philosophy, international relations, and comparative politics.
Ch. 1. Citizenship After Liberalism / Karen Slawner and Mark E. Denham -- Ch. 2. Impossible Citizenship / Roberto Alejandro -- Ch. 3. Taking Multiculturalism Seriously: Political Claims for a Differentiated Citizenship / Matteo Gianni -- Ch. 4. The Politics of Differentiated Citizenship / William J. Meyer -- Ch. 5. Uncivil Society: Liberalism, Hermeneutics and "Good Citizenship" / Karen Slawner -- Ch. 6. Liberal Virtues and Citizen Education / David J. Kahane -- Ch. 7. Educating for Citizenship: Reflections on Pedagogy as Conservation and Critique / Elizabeth Wingrove -- Ch. 8. Justice After Liberalism: Democracy and Global Citizenship / Ed Wingenbach -- Ch. 9. Re-creating Identity After Homo Sovieticus: Language and the Definition of a New Pan-Russianness / Margarita Balmaceda -- Ch. 10. Citizenship and Nationalism: Is Canada a "Real Country"? / Ronald Beiner.
Includes bibliographical references (p. [205]-218) and index.
Keywords: Citizenship; Liberalism; Nationalism